Comparison between embossed digital imaging and unprocessed film-based radiography in detecting periodontal bone defects: an in vitro study - de Molon, Rafael Scaf [UNESP]; Sakakura, Celso Eduardo [UNESP]; Najarro Dearo Morais-Camillo, Juliana Aparecida [UNESP]; de Almeida Junior, Paulo Cesar [UNESP]; Monteiro Loffredo, Leonor de Castro [UNESP]; Scaf, Gulnara [UNESP] (Springer, 2012)
Our aim was to compare bone-loss measurements between embossed digital radiographic imaging and unprocessed film-based radiography.Forty two-wall bone defects were made in the proximal region of the premolar in dry pig mandibles. Digital and conventional radiographs were taken using a Schick sensor and Kodak InSight F-speed intraoral dental film stabilized by a fixing device. Image manipulation was done using Adobe Photoshop 7.0 software with an embossing tool. Four trained examiners made all the radiographic measurements in millimeters a total of three times-from the cementoenamel junction to the most apical extension of the bone loss-with both types of imaging (embossed digital and unprocessed film). As a gold standard, the measurements were also made in dry mandibles using a periodontal probe and digital caliper. Analysis of variance was applied to compare the measurements with both types of imaging and from the dry mandibles. The level of significance was 0.05 for a 95 % confidence interval.The mean values of the measurements for embossed digital imaging, unprocessed film-based imaging, and visual measurement in the dry mandible were, respectively, 5.91, 6.62, and 6.67 mm. There was a statistically significant difference among the three methods (p = 0.007). Tukey's post hoc analysis indicated a similarity between the mean values for unprocessed film-based imaging and dry mandible measurement, but not with embossed imaging.Bone-loss measurement using embossed digital imaging was inferior to unprocessed film-based imaging, and it underestimated the amount of bone loss.
Keywords: Dental radiography; Digital radiography; Radiographic image enhancement; Alveolar bone loss